THE STATUS AND PROSPECTS OF ARTISANAL FISHERIES OF KUBANNI RESERVOIR, ZARIA, KADUNA STATE, NIGERIA - Naallah, D.; Balogun, J.K. (Nigerian Journal of Fisheries, 2019)
Study on the status and prospects of Artisanal fisheries of Kabanni Reservoir, Zaria,Kaduna State, Nigeria was conducted from February 2017 to January 2018. Fish caught by each randomly sampled fishers were identified and sorted according to species and the gear type used. Data were then recorded and analyzed with descriptive statistics (pie charts, frequencies, means, percentages, and standard deviation). A total of fourteen species belonging to seven families were recorded, with family Cichildae having the highest abundance rate. Six fishing villages were located around the reservoir and a total of 17 fishermen were counted as 9 full time and 8 parttime. Majority of the fishermen used the gill net (47.10%) with a catch per unit effort (C.P.U.E.) of 1.73kg/canoe/fisherman. This was followed by the use of hook and line (35.29%) with C.P.U.E. of 2.77kg/canoe/fisherman. While 11.76% used the Malian trap having a C.P.U.E. of 2.85kg/canoe/ fisherman, 5.89% used the cast net having a C.P.U.E. of 1.89kg/canoe. The catch per unit effort was an indication that the Reservoir is productive and can compare favourably with other productive African reservoirs with future prospects.